2023
DOI: 10.3892/mmr.2023.13141
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of salusin‑β downregulates adipoR1 expression to prevent fatty acid oxidation in HepG2 cells

Aohong Xu,
Lei Wang,
Min Luo
et al.

Abstract: Salusin-β and adiponectin receptor 1 (adipoR1) serve important roles in the development of certain cardiovascular diseases and lipid metabolism. However, to the best of our knowledge, the relationship between salusin-β and adipoR1, and their underlying mechanisms of action, currently remain unclear. In the present study, lentiviral vectors designed to overexpress salusin-β or knock down salusin-β expression were used in 293T and HepG2 cells. Semi-quantitative PCR was performed to investigate the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that both Salusin-α and -β are important cardiovascular regulatory peptides and may have opposite effects on lipid metabolism; and there are relatively few studies on the direction of lipid metabolism of Salusin-β, which needs further confirmation. The authors' research group previously found that overexpression of Salusin-β would decrease the expression of AdipoR1 and thus increase lipid accumulation ( 19 ). Salusin-α may serve as a therapeutic target for the management of atherosclerosis, hypertension and other coronary artery diseases by reducing lipid accumulation, reducing vascular endothelial inflammation, and reducing foam cell formation ( 13 - 15 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that both Salusin-α and -β are important cardiovascular regulatory peptides and may have opposite effects on lipid metabolism; and there are relatively few studies on the direction of lipid metabolism of Salusin-β, which needs further confirmation. The authors' research group previously found that overexpression of Salusin-β would decrease the expression of AdipoR1 and thus increase lipid accumulation ( 19 ). Salusin-α may serve as a therapeutic target for the management of atherosclerosis, hypertension and other coronary artery diseases by reducing lipid accumulation, reducing vascular endothelial inflammation, and reducing foam cell formation ( 13 - 15 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study by the authors ( 19 ), the free fatty acid (FFA) group used 200 µ M FFAs to construct the cellular steatosis model. First, a 10 mM oleic acid (OA) stock solution (Shanghai Macklin Biochemical Co., Ltd.) was prepared by fully dissolving OA with NaOH.…”
Section: Methodsmentioning
confidence: 99%